2004
DOI: 10.24200/tjer.vol1iss1pp7-18
|View full text |Cite
|
Sign up to set email alerts
|

Facility Location for Solid Waste Management through Compilation and Multicriterial Ranking of Optimal Decentralised Scenarios: A Case Study for the Region of Peloponesse in Southern Greece

Abstract: Abstract:The present paper addresses the problem of locating solid waste management facilities. Specifically, it studies and proposes optimal alternative solutions for the Greek Region of Peloponnese, by examining facilities for transferring, sorting, treating and landfilling of wastes. Quantitative and qualitative databases concerning the current solid waste management at the Region have been created and used by the model. A customized mixed-integer linear network model has been developed and solved for vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The several possibilities to resolve inconsistency by ELECTRE method have also been reviewed (Mousseau et al, 2003). ELECTRE has been used by researches for the final election of various scenarios for transferring, treating and final disposing the MSW (Perkoulidis et al, 2000;Karagiannidis et al, 2003).…”
Section: Electre IIImentioning
confidence: 99%
“…The several possibilities to resolve inconsistency by ELECTRE method have also been reviewed (Mousseau et al, 2003). ELECTRE has been used by researches for the final election of various scenarios for transferring, treating and final disposing the MSW (Perkoulidis et al, 2000;Karagiannidis et al, 2003).…”
Section: Electre IIImentioning
confidence: 99%
“…Following the results of the MCDA, the study continues with environmental impact assessment (EIA) of the suggested alternative, which presents an interesting approach towards integrated identification of the optimal solution. In addition, Karagiannidis et al (2004) used the ELECTRE methodology in order to compare alternatives for the development of facilities for transferring, sorting, treating and landfilling of wastes at the Region of Peloponnese, Greece, taking also into account current legislation. In the cases of Hokkanen et al (1995) and Hokkanen and Salminen (1994) the ELECTRE III method provided solutions to the problem of choosing solid waste management systems in the region of Oulu, Finland.…”
Section: Use Of Multi-criteria Decision Aid Methods In Different Waste Streamsmentioning
confidence: 99%
“…The ELECTRE family of outranking methods is widely used in literature. Some examples include: the assessment of engineered infrastructure investments [14][15][16][17][18][19][20][21][22][23], the extension of existing planning tools to assess municipal solid waste management based on outranking approaches for MCDM and multi-attribute rating techniques [18,[24][25][26][27][28][29][30], personalised ranking of British Universities [31], investment stock selection [32], sustainable demolition waste management strategy [33], energy systems selection [34], thin-film (TF) PV technology processes [35], urban storm water drainage [27] and housing evaluation [36]. These studies illustrate the potential of outranking methods, particularly ELECTRE tools, to assess and provide insights of complex problems, such as PV systems that are viewed with the different conflicting objectives of the stakeholders.…”
Section: Review On the Application Of Ranking Methodsmentioning
confidence: 99%